Strategi Branding Pendidikan Agama Islam dalam Menyongsong Indonesia Emas 2045: Transformasi Kurikulum, Digitalisasi, dan Penguatan Karakter Generasi Emas - Idris, Fahmi; Saputra, Agi (YASIN, 2025)
Although efforts to strengthen Islamic Religious Education (Pendidikan Agama Islam, PAI) within the framework of national development have been widely discussed, studies that specifically address the gap between the actual condition of PAI and the competency demands of the Indonesia Emas 2045 generation remain limited. This study aims to comprehensively analyze the opportunities and challenges of PAI and to formulate an integrative PAI branding strategy through curriculum transformation, learning digitalization, and the strengthening of character and religious moderation. A qualitative approach was employed using a literature study design based on thematic synthesis, involving 30 scientific and policy documents selected through purposive sampling. Data were collected using document analysis sheets and examined through content analysis, comprising stages of reduction, categorization, interpretation, and source triangulation. The findings indicate that PAI has three main opportunities—character strengthening, learning digitalization, and religious moderation—that are aligned with the vision of Indonesia Emas 2045. However, several significant challenges were identified, including misalignment between the curriculum and twenty-first-century competencies, low levels of teachers’ digital literacy, disparities in educational quality across regions, and a weak public image regarding the effectiveness of PAI. Further analysis identifies six dominant branding strategies, namely curriculum revitalization, enhancement of teacher professionalism, character strengthening, optimization of digital technology, development of life skills, and mainstreaming of religious moderation. This study underscores the importance of repositioning PAI as a strategic pillar of national development and urges policymakers to design systemic, adaptive, and evidence-based branding strategies. Its implications include theoretical contributions to the development of Islamic education branding concepts and practical guidance for schools, teachers, and government in improving the quality of PAI in support of Indonesia Emas 2045.